Survey of Reading Interest of Elementary School Students Towards Picture Story Books: Recommend the Role of School Libraries in Providing Book Collections - Prihantini; Fauziyyah, Hilma Mustika (Journal of Education Research, 2023)
This study aims to describe elementary school students' reading interest in picture story books and the role of school libraries in providing reading materials that follow children's interests. The research location is in Kuningan Regency, West Java, Indonesia. The research method applies a survey with a quantitative approach. The data collection technique used questionnaires distributed to one hundred and thirty-five elementary school students supplemented by interviews. Data analysis applies quantitative descriptive statistical analysis. The results showed that elementary school students reading interest in picture storybooks was high . Of the six sub-variables of reading interest, it was identified that feelings of reading pleasure were high , reading seriousness was high, the ability to understand reading content was high, emotional involvement with the storyline was high, effort to get a medium picture story book, application after reading the story was high. The effort to get a picture book is in the medium category of the six sub-variables. Based on the interview results, students rarely visit the library because the reading materials are primarily textbooks and textbooks. It is recommended that schools establish reading literacy policies and provide a collection of reading books that students are interested.